Demethylation of the NRF2 Promoter Protects Against Carcinogenesis Induced by Nano-SiO2 - Lou, Dan; Wei, Xiaoyi; Xiao, Ping; Huo, Qian; Hong, Xinyu; Sun, Jingqiu; Shuai, Yi; Tao, Gonghua (Frontiers in Genetics, 2020)
Nano silicon dioxide (Nano-SiO2) has been widely used in industries such as the field of biomedical engineering. Despite the existing evidence that Nano-SiO2 exposure could induce oxidative stress and inflammatory responses in multiple organ systems, the carcinogenicity of Nano-SiO2 exposure has rarely been investigated. Thus in this study, two types of human bronchial epithelial cell lines (16HBE and BEAS-2B) were selected as in vitro models to investigate the carcinogenicity of Nano-SiO2. Our results revealed that Nano-SiO2 induces a malignant cellular transformation in human bronchial epithelial cells according to the soft agar colony formation assay. The carcinogenesis induced by Nano-SiO2 was also confirmed in nude mice. By using immunofluorescence assay and high-performance capillary electrophoresis (HPCE), we observed a genome-wide DNA hypomethylation induced by Nano-SiO2. Besides the reduced enzyme activity of total DNMTs upon Nano-SiO2 treatment, altered expression of DNMTs and methyl-CpG binding proteins were observed. Besides, we found that the expression of NRF2 was activated by demethylation of CpG islands within the NRF2 promoter region and the overexpression of NRF2 could alleviate the carcinogenesis induced by Nano-SiO2. Taken together, our results suggested that Nano-SiO2 induces malignant cellular transformation with a global DNA hypomethylation, and the demethylation of NRF2 promoter activates the expression of NRF2, which plays an important role in protecting against the carcinogenesis induced by Nano-SiO2.